Latihan Berjalan Kaki terhadap Perbaikan Profil Lipid pada Wanita Dewasa Kelebihan Berat Badan - Iriyani Harun; Hadi Riyadi; Dodik Briawan; Ali Khomsan (Amerta Nutrition, 2021)
Background: Overweight and obesity are the accumulation of excess fat accumulation which has become a serious problem at the global level, one of which is an abnormality of the lipid profile (dyslipidemia) which is a trigger for cardiovascular diseases such as heart disease and stroke. Physical inactivity is one of the causes of health problems such as obesity and other metabolic disorders. Walking is a moderate-intensity aerobic physical activity suitable for all ages and has a variety of health benefits, especially in less active obese adults. Objectives: The purpose of this study was to examine and analyze walking exercise against changes in the lipid profile of overweight women Discusion: This study is a literature review conducted through online database searches of Scopus, Google Scholar, PubMed, and Science Direct to examine relevant research results regarding the benefits of walking exercise to improve lipid profile. The results showed that walking exercise was able to reduce levels of TC, TG, LDL, and increase serum HDL in overweight and obese patients if it was done with the recommended intensity, duration, and frequencyConclusions: walking exercise is an aerobic physical activity that is suitable for overweight and obese patients and has the potential to improve lipid profiles. This study is expected to be the basis for recommendations to increase daily physical activity for the prevention of cardiovascular disease.